Early modern witches : witchcraft cases in contemporary writing - Gibson, Marion, 1970- (Routledge, 2000)
The sixteen examples collected here describe fifteen English witchcraft cases in detail, vividly recreating events to give the reader the illusion of actually being present at witchcraft accusations, trials and hangings. But how much are we, as readers, victims of literary manipulation by the authors of these texts, and by accusers, magistrates and witches themselves? Some of the writing collected here appear in print for the first time in three centuries, while others are newly edited to give a clearer picture of sources, generic developments in writing about witchcraft, the chronologies of cases, and the biographies of the people who are trying to tell us their stories. Early Modern Witches provides fascinaing insight into both the history of witchcraft and the very thread of cultural history.